Towards a Learning Society: Four Waves Shaping the Future of Lifelong Learning - Leodis Scott (Adult Education Research Conference, 2025)
This paper develops a theory of the learning society through four transformative waves—human potentiality, corporate employability, scholastic inflexibility, and communal responsibility—shaping future paradigms in lifelong learning. By exploring these waves' interconnections, the presentation examines how learning cities and educational democracy can create inclusive, adaptable frameworks for adult and continuing education, fostering global collaboration and unity.
Keywords: learning society; ascension of lifelong learning; learning cities; educational democracy